Analisis Resepsi Konten Pada Akun TikTok @vmuliana Terhadap Kebutuhan Informasi Akan Career Preparation - Uljanatunnisa; Putri, Firly Aldrina (Fakultas Ilmu Komunikasi Universitas Islam Riau, 2023)
The purpose of this research is to examine followers meaning of career information on TikTok accounts using the Stuart Hall reception method. There is an increase in the number of unemployed among the younger generation aged 20-24 years and the low success rate of jobseekers in the selection process is due to their lack of information regarding good career preparation. For this reason, the presence of the @vmuliana TikTok account seeks to provide solutions to all career problems that occur. Researchers focused on the content of the TikTok account @vmuliana regarding career preparation tips needed by students in the playlists